2022
DOI: 10.1039/d2ra04162f
|View full text |Cite|
|
Sign up to set email alerts
|

The role of electrochemical biosensors in SARS-CoV-2 detection: a bibliometrics-based analysis and review

Abstract: This review describes for the first time the role played by electrochemical biosensors in SARS-CoV-2 detection from a bibliometric perspective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 225 publications
0
18
0
Order By: Relevance
“…Moreover, previous research has demonstrated that electrochemical approaches can achieve femtomolar or attomolar concentrations, which is benecial for the clinical diagnosis of infectious diseases. 1,2 Coupling POC devices with miniaturized electrochemical transducers has transformed the detection landscape, enabling real-time, rapid detection of various infectious diseases, including COVID-19, 3 dengue virus (DENV), 4 Zika virus, 5 Inuenza, 6 Hepatitis, 7 human immunodeciency (HIV), 8 Salmonella 9 and Tuberculosis. 10 Electrochemical biosensors rely on changes in measurable redox current due to specic interactions between immobilized biological recognition elements and analytes, such as ssDNA/RNA-ssDNA, aptamer-antigens/proteins, antibodiesantigens, and whole cells-antigen/proteins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, previous research has demonstrated that electrochemical approaches can achieve femtomolar or attomolar concentrations, which is benecial for the clinical diagnosis of infectious diseases. 1,2 Coupling POC devices with miniaturized electrochemical transducers has transformed the detection landscape, enabling real-time, rapid detection of various infectious diseases, including COVID-19, 3 dengue virus (DENV), 4 Zika virus, 5 Inuenza, 6 Hepatitis, 7 human immunodeciency (HIV), 8 Salmonella 9 and Tuberculosis. 10 Electrochemical biosensors rely on changes in measurable redox current due to specic interactions between immobilized biological recognition elements and analytes, such as ssDNA/RNA-ssDNA, aptamer-antigens/proteins, antibodiesantigens, and whole cells-antigen/proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, previous research has demonstrated that electrochemical approaches can achieve femtomolar or attomolar concentrations, which is beneficial for the clinical diagnosis of infectious diseases. 1,2 Coupling POC devices with miniaturized electrochemical transducers has transformed the detection landscape, enabling real-time, rapid detection of various infectious diseases, including COVID-19, 3 dengue virus (DENV), 4 Zika virus, 5 Influenza, 6 Hepatitis, 7 human immunodeficiency (HIV), 8 Salmonella 9 and Tuberculosis. 10…”
Section: Introductionmentioning
confidence: 99%
“…Bortezomib and other boron-containing peptidomimetics, [33,34,35,36] boron nitride (BN) oxide nanosheets, [31] new generation of boron-doped or boron attached composite quantum dots (QDs), [30] combination of 2aminoethyl diphenyl borate with curcumin, [32] dioxaborole compounds, [29] boron-containing nanocages, [37] boron citrate and oleoylethanolamide, [38] biosensors (boron-doped), [39,40,41,42] boron nitride nanosheets (BNNS), [43] 10-vertex boron cage [44] and cobalt (III)-containing BÀ N cluster complexes. [45] The druggability properties of chemical compounds substantially depends on their ADMET properties where ADMET refers to adsorption, distribution, metabolism, extraction and toxicity of molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Boron‐containing compounds (BCCs) are attractive chemicals, some of which reported as COVID‐19 protease inhibitors in the literature. Some of these are: Bortezomib and other boron‐containing peptidomimetics, [33,34,35,36] boron nitride (BN) oxide nanosheets, [31] new generation of boron‐doped or boron attached composite quantum dots (QDs), [30] combination of 2‐aminoethyl diphenyl borate with curcumin, [32] dioxaborole compounds, [29] boron‐containing nanocages, [37] boron citrate and oleoylethanolamide, [38] biosensors (boron‐doped), [39,40,41,42] boron nitride nanosheets (BNNS), [43] 10‐vertex boron cage [44] and cobalt (III)‐containing B−N cluster complexes [45] …”
Section: Introductionmentioning
confidence: 99%
“…Bibliometrics is a quantitative analysis of the literature that provides an understanding of a topic by analyzing the interrelatedness of information in different sections of a paper (e.g., title, keywords, authors, and reference). is analysis technique has been widely used in recent years for systematic reviews of different topics [12][13][14][15][16][17][18]. Bibliometric analyses on tuberculosis have focused on the development of the entire field [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%